An alternative bioassay using Anabas testudineus (Climbing perch) colinesterase for metal ions detection - Ahmad S.A.; Wong Y.F.; Shukor M.Y.; Sabullah M.K.; Yasid N.A.; Hayat N.M.; Shamaan N.A.; Khalid A.; Syed M.A. (Universiti Putra Malaysia, 2024)
Indexed by WOS/SCOPUS